1991
DOI: 10.1042/cs0800249
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Neuropathy on the Microvascular Response to Local Heating in the Human Diabetic Foot

Abstract: 1. The diabetic neuropathic foot exhibits excess arteriovenous anastomotic shunt flow due to a reduced sympathetic vasoconstrictor tone. Local axon reflexes (mediating postural vasoconstriction, for example) are preserved even in severe diabetic neuropathy. This excess shunt flow and its local neurogenic control may be important in the development of complications of the neuropathic limb. 2. The response of arteriovenous anastomoses to local heating was assessed in 13 diabetic patients with neuropathy (12 insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…These studies have demonstrated that both type 1 (insulin dependent) and type 2 (noninsulin dependent) diabetic patients with signs of sensory and/or autonomic neuropathy (e.g., orthostatic hypertension) have increased skin blood flow under basal conditions (2,33) and attenuated reductions in skin blood flow (i.e., vasoconstriction) in response to sympathetic arousal [e.g., produced by mental arithmetic (2) or postural stimuli (29)]. Importantly, deficits in sympathetic vasoconstriction of arterial vessels supplying plantar skin can be demonstrated in both type 1 and type 2 diabetic patients at an early phase of diabetic neuropathy (31,35), perhaps suggesting that sympathetic neurons supplying these vessels are particularly vulnerable to the effects of diabetes.…”
mentioning
confidence: 99%
“…These studies have demonstrated that both type 1 (insulin dependent) and type 2 (noninsulin dependent) diabetic patients with signs of sensory and/or autonomic neuropathy (e.g., orthostatic hypertension) have increased skin blood flow under basal conditions (2,33) and attenuated reductions in skin blood flow (i.e., vasoconstriction) in response to sympathetic arousal [e.g., produced by mental arithmetic (2) or postural stimuli (29)]. Importantly, deficits in sympathetic vasoconstriction of arterial vessels supplying plantar skin can be demonstrated in both type 1 and type 2 diabetic patients at an early phase of diabetic neuropathy (31,35), perhaps suggesting that sympathetic neurons supplying these vessels are particularly vulnerable to the effects of diabetes.…”
mentioning
confidence: 99%
“…Diabetes can be complicated by a range of neurologic, biochemical, inflammatory, and vascular skin deficits that may increase the risk of foot complications (6,9,10,14). Our goal was to determine whether high-risk patients exhibited specific skin structural and functional deficits that could serve as potential biomarkers and may ultimately predispose to foot complications.…”
Section: Discussionmentioning
confidence: 99%
“…The best known is the reduction of peripheral vasoconstriction in response to sympathetic stimuli either on coughing or standing up—the latter in part responsible for orthostatic hypotension. Paradoxical responses also occur—notably, the vasoconstrictor response which takes place on heating rather than the expected vasodilatation,49 and the vascular effects of insulin which lead to a reduction rather than an increase of peripheral vascular resistance and may be the mechanism by which insulin exacerbates orthostatic hypotension 50…”
Section: Neuropathies Of Diabetesmentioning
confidence: 99%